Expanding on the phenotypic spectrum of Woodhouse‐Sakati syndrome due to founder pathogenic variant in DCAF17: Report of 58 additional patients from Qatar and literature review. Issue 1 (30th September 2021) - Ali, Rehab; Al‐Dewik, Nader; Mohammed, Shayma; Elfituri, Mahmud; Agouba, Sahar; Musa, Sara; Mahmoud, Laila; Almulla, Mariam; El‐Akouri, Karen; Mohd, Howaida; Bux, Reem; Almulla, Hajer; et al.
Abstract: Woodhouse‐Sakati syndrome (WSS) is a rare autosomal recessive neuroendocrine and ectodermal disorder caused by variants in the DCAF17 gene. In Qatar, the c.436delC variant has been reported as a possible founder pathogenic variant with striking phenotypic heterogeneity. In this retrospective study, we report on the clinical and molecular characteristics of additional 58 additional Qatari patients with WSS and compare them to international counterparts' findings. A total of 58 patients with WSS from 32 consanguineous families were identified. Ectodermal and endocrine (primary hypogonadism) manifestations were the most common presentations (100%), followed by diabetes mellitus (46%) and hypothyroidism (36%). Neurological manifestations were overlapping among patients with intellectual disability (ID) being the most common (75%), followed by sensorineural hearing loss (43%) and both ID and aggressive behavior (10%). Distinctive facial features were noted in all patients and extrapyramidal manifestations were uncommon (8.6%). This study is the largest to date on Qatari patients with WSS and highlights the high incidence and clinical heterogeneity of WSS in Qatar due to a founder variant c.436delC in the DCAF17 gene. Early suspicion of WSS among Qatari patients with hypogonadism and ID, even in the absence of other manifestations, would shorten the diagnostic odyssey, guide early and appropriate management, and avoid potential complications.